Penerapan Metode Numbered Head Together Dalam Meningkatkan Hasil Belajar Aqidah Akhlak Di MI NW Karang Baru - Ulpa, Mariana; Husairi, Husairi (LP2M STAI Darul Kamal NW Kembang Kerang, 2023)
Abstract The formulation of the problems in this study are (1) How to apply the Numbered Head Together (NHT) model in improving the learning outcomes of the Aqidah Akhlak material Faith to the books of Allah SWT. class IV MI NW Karang Baru? (2) How to increase student learning outcomes by using the Numbered Head Together (NHT) model in the Aqidah Akhlak subject on Faith in the books of Allah SWT. students of class IV MI NW Karang Baru?. This study uses Class Action Research (Class Action Research) as much as two cycles. Each cycle consists of four stages, namely planning, implementing, observing and reflecting. The techniques used in collecting data include tests and interviews. The research results show that the application of the Numbered Head Together (NHT) model can improve students' learning outcomes of the Akhlak Aqidah. This is evidenced by an increase in student learning outcomes from cycle I to cycle II, namely the average score of learning outcomes in the final test of cycle I was 69.70 which was in the category of unfavorable, while in the final test of cycle II was 84.12 and was very good criteria. This shows an increase of 14.42. From these data it can be seen that the application of the Numbered Head Together (NHT) model can improve the learning outcomes of class IV MI NW Karang Baru students